Endoscopic balloon dilatation of Crohn's‐associated intestinal strictures: High patient satisfaction and long‐term efficacy. Issue 6 (1st December 2016) - Rueda Guzmán, Anna; Wehkamp, Jan; Kirschniak, Andreas; Naumann, Aline; Malek, Nisar P.; Goetz, Martin
Abstract : Introduction: Stricture formation is a common long‐term complication of Crohn's disease. Endoscopic balloon dilatation offers a bowel‐sparing treatment option, but long‐term outcome and its association with patient‐, stricture‐, and procedure‐related factors is only poorly understood. Patient satisfaction with endoscopic balloon dilatation is largely unknown. Methods: We performed a retrospective review of all endoscopic balloon dilatation for Crohn's disease‐related strictures between January 2005 and January 2013. Long‐term outcome, complication rates and predictive factors were evaluated. Patient satisfaction was assessed using a questionnaire and telephone interviews. Results: A total of 118 balloon dilatations were performed for 69 strictures in 46 patients. One patient was excluded from further analysis due to malignancy. Median time from diagnosis of Crohn's disease to symptomatic stricture formation was 19 years. Technical success, defined as passage of the endoscope after dilatation, was reportedly obtained in 95 of 106 procedures (89.6%). Two perforations occurred, one of which could be managed conservatively. No episodes of severe bleeding were recorded (procedure‐related complication rate: 2/118; 1.7%). During a median follow‐up of 4.8 years (range 0.4–8.7), 55.6% (25/45) of patients were able to avoid surgery. Of the patients, 35.6% (16/45) did not need any further intervention, 40.0% (18/45) underwent more than one dilatation, and 24.4% (11/45) were operated after the first dilatation. The percentage of patients who were satisfied with the procedure and would again opt for balloon dilation as first line therapy was 83.3% (35/42). None of the risk factors examined in this study correlated with the necessity for subsequent surgery. Discussion: Endoscopic balloon dilatation is a safe and effective first line therapy for Crohn's disease‐related strictures. No technical, stenosis‐, or patient‐related factor reliably predicted sustained dilatation success. Patient satisfaction was high.